From Waste to Energy: Recycling Batik Waste to Electricity - Mujahid, Ahmad; Artika, Miranda Refamala Ayuk; Ramadhani, Trisna Amalia (Proceeding International Conference on Science and Engineering, 2020)
The World’s electricity consumption continues to increase as the shift from conventional products to electronic products weight the electricity burden in every state. Besides that, power outagesinhibitsocial and industrial activities as the last one occurred in Jabodetabek, August 2019. In this research it is pointed out that the composite of batik waste, charcoals, bilimbi, and tamarinds wrapped in aluminium foil is able to generate 0.5-volt electrical voltage per unit. Experiment method is used in this research by involving 13 samples with different compositions to yield a stable electrical voltage. The most stable one is derived from the composition of charcoal, bilimbi, and tamarind with the addition of batik waste water, which generated 0.5volt electrical voltage per unit. In order to verify the generated voltage, an electrical circuit with 7-unit structure was made and examined to a 3-volt flip-flop lamp circuit. To further develop this prototype in a bigger scale, therefore, the supports from various parties are needed for the sake of a continuous research, so that it can give rise to society’s interest to develop environmentally-friendly products and to provide solutions for batik waste water problem that takes place in Sentra Industry Batik, Laweyan, Surakarta that tends to be disposed vainly.